American creative nonfiction / editor, Jay Ellis, University of Colorado at Boulder. - Ellis, Jay, 1963- (Critical insights., 2015)
This book provides an overview of a genre of genres called "creative nonfiction," but also takes a look at lyrical essays. This title begins by figuring out why readers of American literature in particular created "nonfiction" writing and also examines some lyric essayist work whose cannot be trusted as a meaningful form "nonfiction."